Manajemen Sumber Daya Manusia Dalam Pendidikan Islam - Ikri Malia (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Al-Quran is used as a source of Islamic education and other sciences including Islamic education because the Qur'an has an absolute value derived from Allah (God). Allah who created man and he is the one who educates man, so that the content of education has been buried in his revelations. Therefore, there are no problems including Islamic education issues that have been missed from the reach of the Quran. Human resources of good Islamic education is when the human resources of Islamic education is able to formulate plans ahead and be able to make decisions with policies and practices that are appropriate to the situation and conditions encountered in the world Islamic education, so it can be said that without the existence of reliable resources, then the institution of Islamic education will not mean anything and will not give better effect. Islamic educational institution whatever its name and as great as any program, if not supported by its qualified human resources, then the institution will be a difficult institution to develop and progress the program